Consumo de capim-elefante com diferentes idades fornecido para vacas leiteiras - Soares, J. P. G.; Deresz, F.; Salman, A. K. D.; Aroeira, L. J. M.; Oliveira, A. D.; Verneque, R. S.; Berchielli, Telma Teresinha [UNESP] (SciELO Espana/Repisalud, 2009)
The 30, 45 and 60 day-old elephant grasses were evaluated by monitoring their nutritional profile and DM (DMI) and NDF (NDFI) intake by crossbred lactating cows in a 3 × 3 Latin square trial, where the split-plots were the rumen evacuation times: 0, 2, 4 and 6 h after meal. Chemical composition, in vitro dry matter digestibility and ruminal content ranged with grass age. Means (in kg/cow/day) of DMI and NDFI of 30 day-old grass (8.0 and 5.3) were lower than those of grasses with 45 days (10.0 and 6.6) and 60 days (11.0 and 7.3). The maximum of rumen fill was observed at 4:22, 3:55 and 3:49 hours after feeding for treatments with 30, 45 and 60 day-old elephant grass, respectively. Rumen fill did not limit the DMI and NDFI of elephant grass, but the dry matter intake of 30 day-old grass may be affected by the wet content.
Intake of elephant-grass with different ages offered to dairy cows
Keywords: NDF; Rumen evacuation; Rumen fill; Ruminal content; Bos; Pennisetum purpureum; Poaceae